Patterns of inequality of Lithuanian regions - Maknickienė, Nijolė; Lapinskaitė, Indrė; Miečinskienė, Algita; Skačkauskienė, Ilona (Journal of Business Economics and Management, 2018)
Though a country᾽s economy is growing, separate regional development disparities could be even more significant. This paper aims to identify the situation of inequality of Lithuania᾽s regions, taking into consideration the most important factors of regional economic growth and investments. Evaluation of regions by 15 criteria is carried out by a ranking method. Results show a big disparity between regions. Significant Spearman correlation is found between FDI and total investment with all investigated group of factors of economic growth in the group of City Municipalities, but in the group of District Municipalities, it differs. Four scenarios for regional policy formation were distinguished.